Phylogenomics reveal that Mycobacterium kansasii subtypes are species-level lineages. Description of Mycobacterium pseudokansasii sp. nov., Mycobacterium innocens sp. nov. and Mycobacterium attenuatum sp. nov. Issue 6 (4th April 2019) - Tagini, Florian; Aeby, Sébastien; Bertelli, Claire; Droz, Sara; Casanova, Carlo; Prod'hom, Guy; Jaton, Katia; Greub, Gilbert
Abstract : Among the species Mycobacterium kansasii, seven subtypes have been previously reported based on the PCR and the restriction fragment length polymorphism of the gene hsp65 . Here, we used whole-genome sequencing to refine M. kansasii taxonomy and correct multiple inconsistencies. Average nucleotide identity (ANI) values between M. kansasii subtypes ranged from 88.4 to 94.2 %, lower than the accepted 95–96 % cut-off for species delineation. In addition, Mycobacterium gastri was closer to the M. kansasii subtypes 1, 2, 3, 4 and 5 than M. kansasii subtype 6. The recently described species Mycobacterium persicum shared 99.77 % ANI with M. kansasii subtype 2. Consistent with the ANI results, the digital DNA–DNA hybridization value was below the 70 % threshold for species delineation between subtypes and above it within subtypes as well as between subtype 2 and M. persicum . Furthermore, core-genome phylogeny confirmed the current M. kansasii species to be polyphyletic. Hence, we propose (i) Mycobacterium pseudokansasii sp. nov., replacing subtype 3, with the type strain MK142 T (=CCUG 72128 T =DSM 107152 T ), (ii) Mycobacterium innocens sp. nov., replacing subtype 5, with the type strain MK13 T (=CCUG 72126 T =DSM 107161 T ), and (iii) Mycobacterium attenuatum sp. nov., replacing subtype 6, with the type strain MK41 T (=CCUG 72127 T =DSM 107153 T ). Subtype 4 represents a new species-level lineage based on the genomic data but no strain was available. No genome sequence or strain was available for subtype 7. The proposed nomenclature will facilitate the identification of the most pathogenic subtype 1 as M. kansasii by clinicians while the new species names suggest the attenuated pathogenicity of the other subtypes.